Kinetic parameter studies of 6-amino penicillanic acid (6-APA) production by agarose immobilized penicillin acylase in a packed column reactor - Banerjee, Sujoy; Debnath, Mira (2006)
Penicillin acylase, an industrially important biocatalyst catalyzes the conversion of penicillins to 6-amino penicillanic acid (6-APA) which is the main precursor for the production of semisynthetic ÃŸ-lactam antibiotics. The present work involves the continuous production of 6- APA in a packed column reactor by using agarose immobilized penicillin acylase as a block polymer. The strain Escherichia coli ATCC 11105 was used as enzyme source and penicillin G as substrate. Agarose is a natural polymer (carbohydrate) which is cheap, safe and easily available that makes it very suitable for enzyme immobilization. The acidic nature of 6-APA has an inhibitory effect on the enzyme and so the continuous system of production is a better choice. To overcome this problem penicillin acylase was physically entrapped on agarose gel. Kinetic parameters Vmax and Km values were calculated for both native and immobilized enzyme. The native enzyme showed Vmax=3.3Âµmol/min and Km value=18.18mM. The immobilized enzyme was packed in the column reactor to study the kinetic parameters by varying flow rate and different substrate concentration (according to the model of Lily et al 1966). For the immobilized enzyme the Km value=22.22mM. Cmax value was calculated using secondary plot of 1/C versus 1/Q to find the maximum capacity of the bioreactor. This study is very useful and applicable to the industry for the conversion of Penicillin G to 6- APA.